Research on the safety of heavy-liquid-metal-cooled reactors - Gianfelici Simone; Grasso Giacomo (EPJ Nuclear Sciences & Technologies, 2025)
Since the fifth edition, dating 1998 to 2002, the Euratom Framework Programmes have supported numerous collaborative projects dealing with the research and development of the heavy liquid metal technology. In this 20+ year's context of outstanding scoring, LESTO – the latest project recently launched – is taking the baton from PASCAL, about to conclude, with ANSELMUS bridging the gap in between. Both PASCAL and LESTO address (on complementary and synergic topics) key safety-related aspects of the technology, sharing the same foundational approach: advancing on the two pillars of experimental testing and software simulation. The two projects also share the focus on ALFRED and MYRRHA, the two heavy-liquid-metal-cooled reactors included in the strategic roadmap of the European Sustainable Nuclear Industrial Initiative. Thanks to the results generated by the two projects, a significant contribution will be delivered to the substantiation of evidences requested for the licensing of ALFRED and MYRRHA and, in perspective, for that of future heavy-liquid-metal-cooled nuclear systems.